1987
DOI: 10.1172/jci113245
|View full text |Cite
|
Sign up to set email alerts
|

Development of partial tolerance to the gastrointestinal effects of high doses of recombinant tumor necrosis factor-alpha in rodents.

Abstract: Treatment of healthy rats and mice with a single intravenous injection of recombinant human tumor necrosis factor-alpha (rHuTNF-a) caused a dose-dependent gastrointestinal inflammation. Within 30 min gastric emptying was blocked and tissue edema occurred in the small and large intestine. In the cecum hemorrhage occurred after 4 h at doses 2 250 ag/kg. The cecum exhibited an acute inflammatory response following rHuTNF-a treatment similar to that seen in tumor necrosis at the same dose. The vascular endothelium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
39
1
2

Year Published

1989
1989
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(50 citation statements)
references
References 36 publications
8
39
1
2
Order By: Relevance
“…Partial tolerance to the gastrointestinal effects of high rh-TNF-a doses developed when TNF application was repeated daily (Patton et al, 1987). In good agreement with these data haemorrhagic diarrhoea with weight loss developed only after the first TNF application.…”
Section: Resultssupporting
confidence: 78%
“…Partial tolerance to the gastrointestinal effects of high rh-TNF-a doses developed when TNF application was repeated daily (Patton et al, 1987). In good agreement with these data haemorrhagic diarrhoea with weight loss developed only after the first TNF application.…”
Section: Resultssupporting
confidence: 78%
“…In the course of preliminary studies, we found that fed rats were not an appropriate control for the endotoxin-treated rats which, when fed ad libitum, manifested a profound decrease in spontaneous food intake and had distended stomachs with marked food stagnation. This is consistent with the published reports that endotoxin administration constricts the pyloric sphincter and thus inhibits gastric emptying [8,9]. In order to maintain the same post-absorptive state we therefore fasted both the endotoxin-and saline-treated group.…”
Section: Animal Modelsupporting
confidence: 89%
“…Our laboratory (6,7) and others (8)(9)(10) have noted tolerance to the anorectic effects ofTNF with repetitive administration. In addition, we have noted that prior administration of recombinant (r) TNF-alpha also protects against a lethal injection of TNF or a lethal injection of endotoxin (6).…”
Section: Introductionmentioning
confidence: 83%